Osteopontin, a bridge links osteoarthritis and osteoporosis - Bai, Rui-Jun; Li, Yu-Sheng; Zhang, Fang-Jie (Frontiers in Endocrinology, 2022)
Osteoarthritis (OA) is the most prevalent joint disease characterized by degradation of articular cartilage, inflammation, and changes in periarticular and subchondral bone of joints. Osteoporosis (OP) is another systemic skeletal disease characterized by low bone mass and bone mineral density (BMD) accompanied by microarchitectural deterioration in bone tissue and increased bone fragility and fracture risk. Both OA and OP are mainly affected on the elderly people. Recent studies have shown that osteopontin (OPN) plays a vital role in bone metabolism and homeostasis. OPN involves these biological activities through participating in the proliferation, migration, differentiation, and adhesion of several bone-related cells, including chondrocytes, synoviocytes, osteoclasts, osteoblasts, and marrow mesenchymal stem cells (MSCs). OPN has been demonstrated to be closely related to the occurrence and development of many bone-related diseases, such as OA and OP. This review summarizes the role of OPN in regulating inflammation activity and bone metabolism in OA and OP. Furthermore, some drugs that targeted OPN to treat OA and OP are also summarized in the review. However, the complex mechanism of OPN in regulating OA and OP is not fully elucidated, which drives us to explore the depth effect of OPN on these two bone diseases.